Spatial navigation in young versus older adults - Gazova, Ivana; Laczó, Jan; Rubinova, Eva; Mokrisova, Ivana; Hyncicova, Eva; Andel, Ross; Vyhnalek, Martin; Sheardova, Katerina; Coulson, Elizabeth J.; Hort, Jakub (Frontiers in Aging Neuroscience, 2013)
Older age is associated with changes in the brain, including the medial temporal lobe, which may result in mild spatial navigation deficits, especially in allocentric navigation. The aim of the study was to characterize the profile of real-space allocentric (world-centered, hippocampus dependent) and egocentric (body-centered, parietal lobe dependent) navigation and learning in young vs. older adults, and to assess a possible influence of gender. We recruited healthy participants without cognitive deficits on standard neuropsychological testing, white matter lesions or pronounced hippocampal atrophy: 24 young participants (18-26 years old) and 44 older participants stratified as participants 60-70 years old (n=24) and participants 71-84 years old (n=20). All underwent spatial navigation testing in the real-space human analog of the Morris Water Maze, which has the advantage of assessing separately allocentric and egocentric navigation and learning. Of the 8 consecutive trials, trials 2-8 were used to reduce bias by a rebound effect (more dramatic changes in performance between trials 1 and 2 relative to subsequent trials). The participants who were 71-84 years old (p< .001), but not those 60-70 years old, showed deficit in allocentric navigation compared to the young participants. There were no differences in egocentric navigation. All three groups showed spatial learning effect (p´s ≤.01). There were no gender differences in spatial navigation and learning. The linear regression limited to older participants showed linear (β=0.30, p=.045) and quadratic (β=0.30, p=.046) effect of age on allocentric navigation. There was no effect of age on egocentric navigation. These results demonstrate that navigation deficits in older age may be limited to allocentric navigation, whereas egocentric navigation and learning may remain preserved. This specific pattern of spatial navigation impairment may help differentiate normal aging from prodromal Alzheimer’s disease.